284 DO MEDICATIONS GET OPTIMISED DURING AN ACUTE ADMISSION TO HOSPITAL?. (25th October 2022) - MokGatla, O; Haupfear, I; Cafferty, J; Campbell, E; Lavan, AH
Abstract: Background: Potentially Inappropriate Prescriptions (PIPs) and Potential Prescribing Omissions (PPOs) are common in hospitalised older adults and associated with poor outcomes. The aim of this study was to assess whether PIPs and PPOs are reduced during an acute hospital admission. Methods: All inpatients on 5 gerontological wards (1 acute, 1 subacute, 2 rehabilitation, 1 long-stay) on October 31st 2021 were eligible for inclusion. Medical records were retrospectively reviewed. Medication appropriateness was assessed by two assessors at admission and discharge using STOPP/START version 2. Records were consecutively reviewed according to discharge date. Ethical approval was received from the local research and innovation office (ref6275) Results: Of 144 eligible patients, 41 were included; mean age 82.1 (SD6.8) years; 48.8% female, 95.1% under the care of geriatricians. The median length of stay was 24 (IQR10-67.5) days. Mean number of conditions was 5.6 (SD2.9) with dementia present in 22.5%. The mean number of medications increased during admission from 7.2 (SD3.2) to 9 (SD3.1); p=0.006 The number of patients prescribed at least 1 STOPP-PIP reduced by 20.6%; 82.9% (admission) vs 65.9% (discharge), p<0.001. The most common PIPs at were (i) drugs without a clear indication, 34.1% (admission) vs 14.6% (discharge), (ii) high dose proton pump inhibitors, 34.1% (admission) vs 34.1% (discharge) and (iii) Z-drugs in fallers; 17.1% (admission) vs 12.2% (discharge). Of 41 patients, 35 could have START criteria applied. START PPOs were reduced by 53%; 47.2% (admission) vs 22.2% (discharge), p=0.001. The largest improvement was seen in bone absorptive therapy (11.4% (admission) vs 2.9% (discharge) and vitamin d in those experiencing falls/osteopenia; 5.57% (admission) vs 2.9% (discharge). Of the 134 STOPP/START criteria listed, 36 (19.4%) were identified in this cohort. Conclusion: Although the average number of medications increased, PIPs reduced significantly. Only 19.4% of STOPP/START criteria were identified, suggesting that focusing on a number of key PIPs going forward could improve prescribing practices.